Exclusive contracts with complementary inputs - Hiroshi Kitamura; Noriaki Matsushima; Misato Sato (Osaka University, Institute of Social and Economic Research (ISER), 2015)
This study constructs a model of anticompetitive exclusive contracts in the presence of complementary inputs. A downstream firm transforms multiple complementary inputs into final products. When complementary input suppliers have market power, upstream competition within a given input market benefits not only the downstream firm (by lowering the input price) but also complementary input suppliers (by raising complementary input prices). The downstream firm is thus unable to earn higher profits even when socially efficient entry is allowed. Hence, the inefficient incumbent supplier can deter socially efficient entry by using exclusive contracts even in the absence of economies of scale and downstream competition. These results have important implications for antitrust agencies, showing the importance of considering the existence of complementary inputs when examining cases of potential anticompetitive exclusive dealing.
Keywords: L12; L41; L42; 330; Antitrust policy; Complementary inputs; Exclusive dealing; Multiple inputs